Diameter engineering on TiO2 nanorod arrays for improved hole-conductor-free perovskite solar cells. (15th May 2018) - Liu, Wei; Chu, Liang; Hu, Ruiyuan; Zhang, Rui; Ma, Yuhui; Pu, Yong; Zhang, Jian; Yang, Jianping; Li, Xing'ao; Huang, Wei
Highlights: The average diameter of TiO2 NAs were engineered without changing the length. The hole-conductor-free PSCs using TiO2 NAs achieved the efficiency up to 10.15%. The thinner diameter was benefit for better transmission and charge transfer. Abstract: TiO2 nanorod arrays (NAs) have been successfully applied in mesoporous perovskite solar cells (PSCs) due to the direct electron transfer channels, and previous focus has been mainly on the length of TiO2 NAs to improve the performance. To date, diameter engineering without changing length is still a big challenge, which is another key factor on the performance of TiO2 NAs-based PSCs. Here, the diameter of TiO2 NAs was effectively engineered by annealing temperatures from 100 °C to 500 °C to enhance the crystallinity and surface smoothness of TiOx seed-layers, which restrained the transverse direction to decrease the average diameter of TiO2 NAs from 74 to 31 nm via the Steric effect. In addition, the smooth TiOx seed-layers improved the vertical orientation of the TiO2 NAs. The TiO2 NAs were further applied as photoanodes in carbon-based PSCs without hole conductor layers. The fine and vertical TiO2 NAs enhance the performance of PSCs, which mainly results from the improved charge transfer and excellent transmission. The carbon-based PSCs with 31 nm TiO2 NAs achieved the best performance with power conversion efficiency (PCE) up to 10.15%, which is higher than 7.18% of that based on the common TiO2 nanoparticles. Therefore, our findings suggest that the annealing of seed-layers at different temperatures is a feasible and effective strategy to acquire diameter engineering on TiO2 NAs for high performance PSCs.